2020
DOI: 10.1021/acsphotonics.0c01506
|View full text |Cite
|
Sign up to set email alerts
|

Lithography-Free Plasmonic Color Printing with Femtosecond Laser on Semicontinuous Silver Films

Abstract: Plasmonic color printing with semicontinuous metal films is a lithography-free and environment-friendly method for generating non-fading bright colors. Such films are comprised of islands -metal nanoparticles and their clusters of various dimensions, which resonate at different wavelengths upon external light illumination depending on the size and 2 shape of the local particle structures. To experimentally realize systems that were optimized for achieving a broad color range and increased stability, various si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 101 publications
2
19
0
Order By: Relevance
“…Nature provides numerous examples of bright coloration from self-organized photonic crystals . Structural color based on individual resonators, such as plasmonic and dielectric nanoantennas, allows for color printing with subdiffraction resolution. As an alternative method to liquid crystal enabled tuning of plasmonic metasurfaces, , laser printing is a cost-effective postprocessing technique that can tune the plasmonic colors of nanostructure arrays produced by nanofabrication techniques. ,, In contrast, the RLP induced self-organized metasurfaces presented here offer subwavelength resolution without lithography, and it is easy to upscale for large-volume production. To demonstrate the printing resolution of a self-organized structure that can be laser-induced, we pattern an image using the same micron-sized laser focus spot (2–4 μm) and a subdiffraction-limited step size (250 nm) but digitally varied doses according to the gray-scale depth of the image.…”
Section: Resultsmentioning
confidence: 98%
“…Nature provides numerous examples of bright coloration from self-organized photonic crystals . Structural color based on individual resonators, such as plasmonic and dielectric nanoantennas, allows for color printing with subdiffraction resolution. As an alternative method to liquid crystal enabled tuning of plasmonic metasurfaces, , laser printing is a cost-effective postprocessing technique that can tune the plasmonic colors of nanostructure arrays produced by nanofabrication techniques. ,, In contrast, the RLP induced self-organized metasurfaces presented here offer subwavelength resolution without lithography, and it is easy to upscale for large-volume production. To demonstrate the printing resolution of a self-organized structure that can be laser-induced, we pattern an image using the same micron-sized laser focus spot (2–4 μm) and a subdiffraction-limited step size (250 nm) but digitally varied doses according to the gray-scale depth of the image.…”
Section: Resultsmentioning
confidence: 98%
“…26 The Ag NPs present in the OM solution were modified by laser irradiation, resulting in various sizes and shapes of Ag NPs according to the processing conditions. The size and shape control of these Ag NPs can shift the reflectance dip of plasmonic NP structure; 19,22 thus, various colors can be realized simply through process control. Moreover, the relatively weak particle-to-particle bonding of the unpatterned regions aids easy removal thereof by an organic solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18 From the different chemical and optical properties of the additional layer, improved performance can be achieved with a simple pretreatment. Since oxidation-induced degradation can also occur in plasmonic printing based on Ag NPs, 19 the application of an additional layer will be the focus of future work for stable printing with the expanded color span. Scanning electron microscopy (SEM) measurements confirmed that this coloration was caused due to the morphological variations in the laser-induced Ag nanoseeds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, structural color based on photonic structures has attracted extensive attention due to high resolution, [ 1,2 ] strong stability, [ 3–5 ] and easy production of compact monolithically integrated devices, [ 6,7 ] These attributes have rendered structural colors of great interest to printing, [ 1,2 ] display, [ 8,9 ] imaging, [ 10,11 ] decoration, [ 12,13 ] colorimetric sensing, [ 14–17 ] and more importantly, anti‐counterfeiting, [ 9 ] and encryption, [ 18–20 ] Many methods have produced vivid structural colors such as multilayer interference, [ 21–25 ] photonic crystals, [ 26 ] guided mode resonances, [ 27 ] plasmonic resonances, [ 12,28,29 ] and Mie scattering. [ 6,30 ] Especially, thin‐film‐based structural colors such as metal‐insulator‐me`tal (MIM) cavities, [ 8 ] lossy film cavities, [ 23 ] and multilayer [ 21 ] film systems have been implemented for the simplest fabrication and integration on a large scale.…”
Section: Introductionmentioning
confidence: 99%